2019
DOI: 10.1103/physrevlett.122.206401
|View full text |Cite
|
Sign up to set email alerts
|

Topological Axion States in the Magnetic Insulator MnBi2Te4 with the Quantized Magnetoelectric Effect

Abstract: Topological states of quantum matter have attracted great attention in condensed matter physics and materials science. The study of time-reversal-invariant topological states in quantum materials has made tremendous progress. However, the study of magnetic topological states falls much behind due to the complex magnetic structures. Here, we predict the tetradymite-type compound MnBi2Te4 and its related materials host topologically nontrivial magnetic states. The magnetic ground state of MnBi2Te4 is an antiferr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
567
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 749 publications
(607 citation statements)
references
References 61 publications
27
567
2
11
Order By: Relevance
“…As a consequence, the ground state of EuCd 2 As 2 becomes a novel axion insulator state which is not studied in previous theoretical paper 14. This ground state is similar to that reported recently in the MnBi 2 Te 4 family 17,18. But for EuCd 2 As 2 , massless Dirac surface states appear on some specifically oriented surfaces which are protected by the mirror or TL symmetries.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thesupporting
confidence: 79%
See 1 more Smart Citation
“…As a consequence, the ground state of EuCd 2 As 2 becomes a novel axion insulator state which is not studied in previous theoretical paper 14. This ground state is similar to that reported recently in the MnBi 2 Te 4 family 17,18. But for EuCd 2 As 2 , massless Dirac surface states appear on some specifically oriented surfaces which are protected by the mirror or TL symmetries.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thesupporting
confidence: 79%
“…Furthermore, it was shown that for other surfaces, there are gaped surface states contributing to half‐quantized anomalous Hall conductivity. This class of AFM materials was coined as AFM TIs, and as a possible candidate for an axion insulator, as reported recently for MnBi 2 Te 4 17–21. However, the topological nature of the surface of MnBi 2 Te 4 remains puzzling due to disagreements between experimental results and theoretical predictions 19–21.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thementioning
confidence: 95%
“…To date the closest to a physical realization seems to the antiferromagnetic topological insulator 28 MnBi 2 Te 4 , which has been the subject of much recent interest. [29][30][31][32][33][34] Other symmetry operations also reverse the sign of θ, and thus support an axion Z 2 classification. These include simple mirrors and glide mirrors, rotoinversions, and time-reversed rotations and screws.…”
Section: Introductionmentioning
confidence: 75%
“…Generally, after sample cleavage, the new surface of bulk MnBi 2 Te 4 is divided into two parts (layers) according to the depth from the topmost layer (see schematic in Fig. 4D): (i) the top layer with the thickness of few nanometers, which hosts an embedded Dirac cone structure due to the unclear magnetic order (26,27,38); (ii) the deep layer with the predicted out-of-plane antiferromagnetic order (18,19). Depending on the detection depths of different techniques, the top layer is detectable to surface sensitive techniques, such as STM and ARPES, while the deep intrinsic layer is detectable to bulk sensitive techniques such as transport measurements.…”
Section: Figurementioning
confidence: 99%
“…For example, the observations of magnetism-induced gap opening at the Dirac point are either too large or too small (absent) (17)(18)(19)(23)(24)(25)(26)(27)(28) and the assignment of the topological surface states are still controversial (26)(27)(28). Here we employ scanning tunneling microscopy (STM) to systematically study the electronic structure of MnBi 2 Te 4 in both real and momentum spaces, and the complementary information helps us to have a better understanding of the material.…”
Section: Introductionmentioning
confidence: 99%